Sebuah Analisis Konservasi Ekosistem Hutan Mangrove Daerah Pesisir Kampung Nipah Kecamatan Perbaungan - Meilinda Suriani Harefa; Bobby Josep Triady Pangaribuan; Amri S; Andre K. (Jurnal Georafflesia: Artikel Ilmiah Pendidikan Geografi, 2020)
The geographical condition of the State of Indonesia has great potential in the coastal area which refers to the mangrobve ecosystem area. The occurrence of land use change has an impact on mangrove damage in various areas and results in reduced mangrove land. The purpose of this study was to determine the condition of the mangrove ecosystem in Nipah Village, Sei Nagalawan Village, to see the potential of the mangrove forest ecosystem that can help the environment and the community and to analyze conservation techniques in the mangrove ecosystem in Sei Nagalawan Village, Perbaungan District. The research was conducted using observation and interview techniques to obtain primary data and conduct literacy for secondary data, then conduct qualitative descriptive analysis by providing an overview of the research results. The results showed (1) the condition of the mangroves was in good condition with a variety of mangrove types, namely there were 8 types of mangroves in the mangrove forest ecosystem of Nipah Village, Sei Nagalawan Village, Perbaungan District with good living conditions but there were different living environments, namely in the sand environment and the mud environment. experience different growth processes. (2) the potential of the mangrove ecosystem is divided into several functions, namely an ecological function as an abrasion barrier and a biological function as a spawning location, an economic function that is to increase the community's economy through the management of the potential of the mangrove forest ecosystem into food, medicinal ingredients with various types of mangroves that can be used. (3) The Mangrove Forest Conservation is carried out by the community and the local government and also involves various NGOs and student communities among students and lecturers. Where conservation is carried out by means of rehabilitation, responsibility, and responsiveness..